Deciphering the Origin of the First Steps in the Degradation of Azo Dyes: A Computational Study - Cardenas-Jiron, G; Pino-Lopez, E; Pino-Rios, R (2024)
Azo dyes find applications across various sectors including food, pharmaceuticals, cosmetics, printing, and textiles. The contaminating effects of dyes on aquatic environments arise from toxic effects caused by their long-term presence in the environment, buildup in sediments, particularly in aquatic species, degradation of pollutants into mutagenic or mutagenic compounds, and low aerobic biodegradability. Therefore, we theoretically propose the first steps of the degradation of azo dyes based on the interaction of hydroperoxyl radical (•OOH) with the dye. This interaction is studied by the OC and ON mechanisms in three azo dyes: azobenzene (AB), disperse orange 3 (DO3), and disperse red 1 (DR1). Rate constants calculated at several temperatures show a preference for the OC mechanism in all the dyes with lower activation energies than the ON mechanism. The optical properties were calculated and because the dye-•OOH systems are open shell, to verify the validity of the results, a study of the spin contamination of the ground [Formula: see text] and excited states [Formula: see text] was previously performed. Most of the excited states calculated are acceptable as doublet states. The absorption spectra of the dye-•OOH systems show a decrease in the intensity of the bands compared to the isolated dyes and the appearance of a new band of the type π → π* at a longer wavelength in the visible region, achieving up to 868 nm. This demonstrates that the reaction with the •OOH radical could be a good alternative for the degradation of the azo dyes. © 2023. The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.